Makan sebagai Aktivitas Produktif: Tinjauan Filosofis tentang Makan dari Perspektif Foucaultian - Setiawan, F. X. Rudi (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2015)
The meaning of eating is often reduced to concern objects or properties. Food is quite often understood as merely nutritive materials to fulfill the biological needs in order to survive or to satisfy human psychological desire. From this perspective, eating is tragically seen as killing for living. Eating thus becomes a consumptive and exploitative action. Nevertheless, eating can be a more productive act if food is not only construed as object or property, but as human strategy or means to construct relationships in social life. Inspired by Foucault, this paper shows that the meaning of food ought to be extended from the nutritive intrinsic aspects toward the political or cultural aspects; that is, food as a means to construct subject. In a sense, food governs or normalizes people in their social life. Therefore, food and eating give rise to knowledge, value order, behavioral patterns, lifestyles, or beliefs: they become the creative and transformative energy of the civilization.